2021
DOI: 10.1080/07350015.2020.1865169
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Subjective Well-Being Data with Misclassification

Abstract: We use novel nonparametric techniques to test for the presence of nonclassical measurement error in reported life satisfaction (LS) and study the potential effects from ignoring it. Our dataset comes from Wave 3 of the UK Understanding Society that is surveyed from 35,000 British households. Our test finds evidence of measurement error in reported LS for the entire dataset as well as for 26 out of 32 socioeconomic subgroups in the sample. We estimate the joint distribution of reported and latent LS nonparametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…As noted above, ordinal data are also most appropriate. It could also be used as an alternative to frequentist approaches to solve misclassification (for example, Oparina and Srisuma [2022]). In Operina and Srisuma (2022) and other similar approaches, instrumental variables or other specific benchmarks are required, and this is not always feasible for every study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, ordinal data are also most appropriate. It could also be used as an alternative to frequentist approaches to solve misclassification (for example, Oparina and Srisuma [2022]). In Operina and Srisuma (2022) and other similar approaches, instrumental variables or other specific benchmarks are required, and this is not always feasible for every study.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be used as an alternative to frequentist approaches to solve misclassification (for example, Oparina and Srisuma [2022]). In Operina and Srisuma (2022) and other similar approaches, instrumental variables or other specific benchmarks are required, and this is not always feasible for every study. The Bayesian approach in this article allows users to “model their way out” of misclassification biases.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of job satisfaction are, by construction, ordinal in nature, and the mean ranking of ordinal variables is difficult to identify (Oparina and Srisuma, 2022). Bond and Lang (2019) argue that the ranking of the means can be identified only if the distribution of well-being states for one group of individuals first-order stochastically dominates that of the other.…”
Section: Correlation Analysismentioning
confidence: 99%
“…By replicating prior studies, the authors showed that key estimated parameters varied by up to 100% due to data errors. Other papers also indicated errors in aggregate statistical data for suicide [14], disability [15], mortality [16], and life satisfaction [17]. Thus, despite the fact that many studies have examined methods of correcting classification bias [9], [11], we can conclude based on previously mentioned cases that it is essential to analyze this bias together with a mathematical formula 1 for calculating the indicator for social indicators research.…”
Section: Introductionmentioning
confidence: 99%